Editorial - Mattos, Amana; Jacó-Vilela, Ana Maria; Mendes, Deise Maria Fernandes; Ribeiro, Heloisa Fernandes Caldas; Hernández, Jimena de Garay; Quadros, Laura Cristina de Toledo; Quitério, Patrícia Lorena; Leme, Vanessa Barbosa Romera; Darriba, Vinicius Anciães (Estudos e Pesquisas em Psicologia, 2020)
Amana Mattos, Ana Maria Jacó Vilela, Deise Maria Fernandes Mendes, Heloisa Fernandes Caldas Ribeiro, Jimena de Garay Hernández, Laura Cristina de Toledo Quadros, Patrícia Lorena Quitério, Vanessa Barbosa Romera Leme, Vinicius Anciães Darriba